On the lexical nomination of things and objects - Sadziński, Witold (Acta Universitatis Lodziensis. Folia Germanica, 2023)
The basic part of the article is devoted to the nature and the modalities of use of eponyms, whereby terminological problems are also touched upon – preferably against the background of a contrastive analysis, which is also only implicit. In this context, a consistent differentiation is made between eponyms and deonyms in order to accommodate the disambiguation needs of the former in German. The use of deonyms will be exemplified primarily on the basis of scientific and culinary terminology, where deonyms (in part) perform different functions in each case.